Customer-centric marketing strategies tools for building organizational performance - Kaufmann, Hans Rüdiger 1958-; Mohammad Fateh Ali Khan Panni 1981- (Premier reference source, 2013)
"This book provides a conceptual understanding on customer-centric marketing strategies as well as revealing the success factors of these concepts with a goal to improve the organization’s financial and marketing performance" - Provided by publisher